Masyarakat Blitar Selatan Sebagai Subyek Agonistik Mouffian Dalam Demokrasi Indonesia - Rohman, Miftahul; Puspitasari, Ravika Alvina (Universitas Islam Negeri Raden Intan Lampung, 2024)
Citizenship status in Indonesia is influenced by strong religious politics. In Indonesia's political history, the status of citizens is largely determined by religious identity. This then has an impact on the rights that can be obtained and accessed by the community. The people of South Blitar, in particular, have experienced the dynamics of citizenship caused by the dynamics of religious politics in Indonesia since the events of 1965. This article uses Chantal Mouffe's political analysis to look at the historical facts experienced by community groups in Indonesian democratic politics. This article finds that the South Blitar community as a citizen entity can become a citizen who is able to emerge its identity as a subject in the midst of plurality. Furthermore, the people of South Blitar can appear as agonistic subjects so that they must remain in Indonesia's very heterogeneous democracy.